Mapping Bokoni: Exploring Bokoni settlement choices and changes in Mpumalanga and Limpopo, South Africa using GIS site distribution analysis techniques - Schoeman, M.H (2026)
Dissertation (MA (Archaeology))--University of Pretoria, 2016.